Source apportionment of marine atmospheric aerosols in northern South China Sea during summertime 2018. (15th November 2021) - Liang, Baoling; Cai, Mingfu; Sun, Qibin; Zhou, Shengzhen; Zhao, Jun
Abstract: Marine atmospheric aerosols play important roles in the global radiation balance and climate change. Hence, measuring physiochemical aerosol properties is essential to better understand their formation, aging processes, and source origins. However, high temporal resolution measurements of submicron particles are currently scarce in the northern South China Sea (SCS). In this study, we conducted a ship-based cruise campaign with a scanning mobility particle sizer and an online time of flight aerosol chemical speciation monitor to measure the particle number size distribution (PNSD) and the chemical composition of submicron particles over the northern SCS during summer 2018. The mean concentration of non-refractory submicron particulate matter (NR-PM1 ) was generally 9.11 ± 4.86 μg m −3 ; sulfate was the most abundant component, followed by organics, ammonium, nitrate, and chloride. Positive matrix factorization (PMF) analysis was applied to the PNSD (size PMF) and organic aerosols (OA PMF) and further investigated the source apportionment of the submicron particles. The size PMF identified four factors, including ship exhaust, ship influencing marine primary, continent affected marine secondary, and mixed accumulation aerosols. The most abundant particles in the number concentration were associated with ship emissions, which accounted for approximately 44 %. The submicron organic aerosols were highly oxidized and composed of low-volatility oxygenated OA (LV-OOA, 68 %), semi-volatile OOA (SV-OOA, 21 %), and hydrocarbon-like OA (HOA, 11 %). The backward trajectory of air masses showed that the northern SCS was most frequently (64.7 %) influenced by air masses from the Indo-Chinese Peninsula (ICP) during the campaign, implying that pollutants from ICP have a significant impact on the atmosphere of the northern SCS during summer. Thus, in situ ship-based cruise measurements can provide valuable data on the physiochemical characteristics of marine atmospheric aerosols to better understand their source origins. Graphical abstract: Image 1 Highlights: Ship emissions contribute significantly to aerosol numbers in South China Sea (SCS). Pollutants from Indo-Chinese Peninsula affect most frequently SCS during summer. Submicron particle concentration in SCS resembles Mediterranean, but exceeds others. Organic aerosol in SCS is highly oxidized in comparison to North Pacific and Arctic.